MINUMAN INSTAN DARI RIMPANG BANGLE (Zingiber cassumunar Roxb.) DENGAN PENAMBAHAN KULIT KAYU MANIS (Cinnamomum burmanii - Zulhamdi Sumitro; Noviar Harun; Raswen Efendi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Bangle rhizome plant is a medicinal plant that is often used as medicinal drugs because it contains flavonoid compounds. The purpose of this research is to get the right ratio between bangle rhizome and cinnamon bark so as to produce instant drink with good quality.This experiment was conducted experimentally using Completely Randomized Design (RAL) with 4 treatments and 4 replications and followed by Duncan's New Multiple Range Test (DNMRT) test at 5%. The treatments were BK1 (90:10), BK2 (80:20), BK3 (70:30), and BK4 (60:40). The results of the study, treatment of BK4 is the best treatment is the best treatment including 1,71% moisture content, ash content of 1,37%, total sugar content 44,28, antioxidant levels 97.89 ppm, and sensory assessment is relatively preferable, especially in the aroma and taste. Keywords: Instant Drinks, Rhizome Bangle, Cinnamon Bark